Development of methods of artillery control for suppression of an enemy amphibious operation in video game simulations - Grishyn, Maksym; Maksymova, Oksana; Kirkopulo, Kateryna; Klymchuk, Oleksandr (Technology audit and production reserves, 2025)
The paper describes the tactical methods of using artillery guns for counter-amphibious in deep and shallow water landscapes. The study's object is to model military game scenarios, in particular, the role of artillery forces in countering an amphibious operation of one or two divisions. One of the most problematic areas is combining continuous fire support and maneuvering to maintain artillery survivability and save ammunition with limited resources. The study used mathematical models of combat resource utilization based on Markov chains, taking into account the probabilistic aspects of target destruction. Simulation models were also developed for various scenarios of countering amphibious assault ships, which allows for optimizing the number of shells and determining the most effective moments for opening fire. Several approaches to firing have been developed and analyzed: methods of minimizing the number of shells, rapid neutralization of enemy targets, and mixed methods that allow finding a balance between minimizing resources and speed of response. Each method has its advantages depending on the combat situation: cost minimization methods are suitable for controlled scenarios. Instead, methods of rapid destruction are effective in high-risk situations but require more resources. A new mixed tactical method has been developed. This is because the proposed methods have several features, in particular, a large discrepancy in the predicted minefield, which also made it possible to assess the ability to hold the minefield of the fairway, which is important for protection against further attacks. This ensures the possibility of obtaining a high level of minefields on the fairway (up to 67.77 %). Compared to similar indicators, which ranged from 46.42 % to 67.77 %, but without specifying the method, this provided advantages in the form of the possibility of tactical maneuvering between the proposed methods, depending on the current state of resources and the proximity of enemy targets.